Azacitidine and Venetoclax in Previously Untreated Acute Myeloid Leukemia - DiNardo, Courtney D; Jonas, Brian A; Pullarkat, Vinod; Thirman, Michael J; Garcia, Jacqueline S; Wei, Andrew H; Konopleva, Marina; Döhner, Hartmut; Letai, Anthony; Fenaux, Pierre; Koller, Elizabeth; Havelange, Violaine; et al. (The New England journal of medicine, 2020)
BACKGROUND: Older patients with acute myeloid leukemia (AML) have a dismal prognosis, even after treatment with a hypomethylating agent. Azacitidine added to venetoclax had promising efficacy in a previous phase 1b study. METHODS: We randomly assigned previously untreated patients with confirmed AML who were ineligible for standard induction therapy because of coexisting conditions, because they were 75 years of age or older, or both to azacitidine plus either venetoclax or placebo. All patients received a standard dose of azacitidine (75 mg per square meter of body-surface area subcutaneously or intravenously on days 1 through 7 every 28-day cycle); venetoclax (target dose, 400 mg) or matching placebo was administered orally, once daily, in 28-day cycles. The primary end point was overall survival. RESULTS: The intention-to-treat population included 431 patients (286 in the azacitidine-venetoclax group and 145 in the azacitidine-placebo [control] group). The median age was 76 years in both groups (range, 49 to 91). At a median follow-up of 20.5 months, the median overall survival was 14.7 months in the azacitidine-venetoclax group and 9.6 months in the control group (hazard ratio for death, 0.66; 95% confidence interval, 0.52 to 0.85; P<0.001). The incidence of complete remission was higher with azacitidine-venetoclax than with the control regimen (36.7% vs. 17.9%; P<0.001), as was the composite complete remission (complete remission or complete remission with incomplete hematologic recovery) (66.4% vs. 28.3%; P<0.001). Key adverse events included nausea of any grade (in 44% of the patients in the azacitidine-venetoclax group and 35% of those in the control group) and grade 3 or higher thrombocytopenia (in 45% and 38%, respectively), neutropenia (in 42% and 28%), and febrile neutropenia (in 42% and 19%). Infections of any grade occurred in 85% of the patients in the azacitidine-venetoclax group and 67% of those in the control group, and serious adverse events occurred in 83% and 73%, respectively. CONCLUSIONS: In previously untreated patients who were ineligible for intensive chemotherapy, overall survival was longer and the incidence of remission was higher among patients who received azacitidine plus venetoclax than among those who received azacitidine alone. The incidence of febrile neutropenia was higher in the venetoclax-azacitidine group than in the control group. (Funded by AbbVie and Genentech; VIALE-A ClinicalTrials.gov number, NCT02993523.).
Keywords: recidiva; Bridged Bicyclo Compounds, Heterocyclic; Leukemia, Myeloid, Acute; azacytidin; bicyklické sloučeniny heterocyklické; Humans; lidé středního věku; leukopenie; analýza podle původního léčebného záměru; Double-Blind Method; Leukopenia; pneumonie; Aged; Female; sulfonamidy; protokoly protinádorové kombinované chemoterapie; trombocytopenie; Thrombocytopenia; senioři; dvojitá slepá metoda; lidé; Sulfonamides; indukce remise; Follow-Up Studies; ženské pohlaví; Kaplanův-Meierův odhad; Pneumonia; Male; Middle Aged; Antineoplastic Combined Chemotherapy Protocols; Remission Induction; Aged, 80 and over; Azacitidine; Intention to Treat Analysis; Recurrence; senioři nad 80 let; Kaplan-Meier Estimate; mužské pohlaví; akutní myeloidní leukemie; následné studie